An Adaptive Blended Learning in English Language Teaching - Puspitasari, Desi; Hanayanti, Citra Siwi (Institut Agama Islam Negeri Ponorogo, 2023)
The post-Covid-19 outbreak exposes vulnerabilities in the educational system. The learning process shifts from online to blended learning. This article aims to describe the process of adapting blended learning for English education students. This article discusses the process of applying blended learning to English education students, the difficulties of doing so, and the impact on students who learn using blended learning at IAIN Ponorogo. This research was conducted on 6th-semester English education students at IAIN Ponorogo. The findings of this study show that the lectures were conducted in blended learning in the English education department at IAIN Ponorogo. The students said that blended learning helps them to understand the material easily. The finding of this study also revealed a positive impact experienced by students. Adaptive blended learning provides the students with new experiences as it combines virtual face-to-face learning and classroom interaction.